Bis[(4-methylphenyl)ethynyl] telluride - Caracelli, I.; Zukerman-Schpector, J.; Pena, J.M.; Stefani, H.A.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The tellurium atom in the title bis-ethynyl telluride, Te(C9H7)(2) or C18H14Te, is located on a crystallographic twofold axis, the C-Te-C angle being 92.23 (15)degrees. The dihedral angle between the rings is 87.27 (7)degrees. In the crystal structure, molecules are connected in chains parallel to the b axis and mediated by C-H center dot center dot center dot pi interactions.